Application of an indentation sensor for the arthroscopic measurement of articular cartilage stiffness. (April 2022) - Kitta, Yuki; Kiriyama, Yoshimori; Harato, Kengo; Kobayashi, Shu; Niki, Yasuo; Matsumoto, Morio; Nakamura, Masaya; Nagura, Takeo
Direct measurement of cartilage stiffness provides useful clinical information and enables us to develop treatment strategies for patients. We applied an indentation sensor to evaluate cartilage stiffness under arthroscopic control. The purpose of this study was to validate the arthroscopic indentation sensor using cadaver knees and to measure cartilage stiffness in clinical cases. The stiffness of a material with known properties was measured at thicknesses from 2 mm to 10 mm with a 2-mm interval. This was repeated three times at each thickness to evaluate repeatability. The articular cartilage stiffness of the medial and lateral femoral condyles of five human cadaveric knees was measured. The sensor was inclined from 0° to 20° with 1° intervals. The stiffness value at each degree of inclination was compared to evaluate the acceptable measuring angle. Additionally, articular cartilage stiffness was measured in 23 adolescent and 11 adult patients under arthroscopy. Young's moduli of the material were 1.15–1.24 (mean 1.20) MPa. Inter-class correlation coefficients in repeated measurements using the material were 0.83–0.99. There were no differences in the cartilage stiffness between the medial and lateral femoral condyles of the cadaver knees. All condyles showed a nonlinear relationship between force and displacement. The force decreased in all condyles when the tip of the sensor system was tilted. The range of error was < 97.1% within 5° inclination. There was a moderate negative correlation between age and cartilage stiffness in adolescent patients, and a moderate positive correlation in adult patients. Since the sensor system is manually held during measurement, the validity and repeatability to assess material properties of the cartilage may be inaccurate. This study has proven that the instrument can measure the stiffness of joint cartilage reliably and is a useful clinical tool under arthroscopic control.